The Role of Corporate Social Responsibility in Enhancing Socio-economic Prosperity of the Third-Gender (Hijra) Community in Bangladesh - Mohammad Faruk Hossain (Asean Social Work Journal, 2026)
Corporate Social Responsibility (CSR) is a concept that enables corporations to play an active role in social development beyond their economic goals. This study focuses on how CSR is engendered as a means to increase the socio-economic well-being of the third-gender (hijra) in Bangladesh, which is a minority and socially marginalised group in the country who are constantly excluded from work, health, education and social engagement. The study uses a qualitative doctrinal research approach, focusing on reading the literature and analysing academic, policy, legal, and selected CSR case studies relevant to Bangladesh. It reviews CSR contributions across employment, skills development, health care access, education, and community inclusion, with a focus on the hijra population. The findings suggest that CSR programmes will be of significant value in creating employment, providing vocational training, supporting education, offering healthcare programmes, and integrating supramicrosocietal practices to meet the socio-economic needs of the hijra community. The study also concludes that alliances among corporate, government, and Non-Governmental Organisation (NGO) actors enhance the sustainability and effectiveness of such interventions. The study concludes by suggesting applying CSR as a tool for inclusive development and social justice in Bangladesh, achieved through a well-informed, participatory, and long-term approach focused on the specific challenges faced by the hijra community